2011
DOI: 10.2175/193864711802765976
|View full text |Cite
|
Sign up to set email alerts
|

Removing Hydrogen Sulfide from Digester Gas Using Aerobic and Anoxic Biotrickling Filters

Abstract: The Sanitation Districts of Los Angeles County (Districts) have been using ferrous chloride (FeCl 2 ) to control the hydrogen sulfide (H 2 S) concentration in digester gas at the Joint Water Pollution Control Plant (JWPCP) for over 30 years. Although FeCl 2 has been very effective in controlling digester H 2 S levels, the cost of this chemical has increased significantly in the last few years. Consequently, the Districts initiated a study to investigate the use of biotrickling filters (BTFs) to control digeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…At the BBWWTP, H 2 S removal performance is typically established within 12 to 24 hours after recirculation and aeration commences. To date, the BBWWTP biological H 2 S scrubbers support pilot test data (Soroushian et al 2006;and Lee et al 2011) and have demonstrated good H 2 S removals from the digester gas. In November 2011, as part of the Source Emission Survey (Maxxam, 2011) gas samples were taken at the inlet and outlet of the H 2 S scrubber at three separate sampling times about one hour apart.…”
Section: Biological H 2 S Scrubbermentioning
confidence: 85%
“…At the BBWWTP, H 2 S removal performance is typically established within 12 to 24 hours after recirculation and aeration commences. To date, the BBWWTP biological H 2 S scrubbers support pilot test data (Soroushian et al 2006;and Lee et al 2011) and have demonstrated good H 2 S removals from the digester gas. In November 2011, as part of the Source Emission Survey (Maxxam, 2011) gas samples were taken at the inlet and outlet of the H 2 S scrubber at three separate sampling times about one hour apart.…”
Section: Biological H 2 S Scrubbermentioning
confidence: 85%